Innovation of Tonjangpis Abon in An Integrated Stunting Prevention Movement in the Healthy Kitchen Anti-Stunting Program - Sagala, Lam Murni Br; Tambunan, Dior Manta; Sinaga, Nelly Dameria (Indonesian Journal of Global Health Research, 2024)
Stunting is a chronic condition that describes impaired growth due to long-term malnutrition. It is one of the consequences of malnutrition experienced by toddlers (children under five years old). It causes children to fail to grow and are too short for their age due to a lack of nutritional needs, namely protein sources. Toddlers who experience stunting will have suboptimal intelligence levels, be more susceptible to disease, and be at risk of mental retardation as well as decreasing productivity levels in the future. The occurrence of stunting in Indonesia is a recurring problem, and there is a fairly high prevalence of stunting each year in North Sumatra, Medan Belawan District. This study aims to determine the effect of the innovation of Tonjangpis abon (a combination of mackerel tuna and banana blossom floss) in an integrated stunting prevention movement on weight gain in 2-3-year-old children in Belawan I District. This is a quasi-experimental study with a one-group pre-test and post-test design. The research population was undernourished toddlers aged 12-36 months in Belawan I District, with a total sampling technique of 16 undernourished toddlers aged 12-36 months. The result shows a p-value of 0.004, which means there is a significant effect of Tonjangpis abon innovation in an integrated stunting prevention movement on weight gain in 2-3-year-old children.